Pemberdayaan Masyarakat dan Peningkatan Kualitas Pendidikan Serta Optimalisasi Potensi UMKM Lokal melalui Produk dan Pemasaran di Desa Besar II Terjun - M. Fiqri Basyir; Nadlrah Naimi (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
Independent Community Service (KKN) in Desa Besar II Terjun by students of the Faculty of Islamic Studies, University of Muhammadiyah North Sumatra aims to improve the quality of education and optimize MSMEs. Through an in-depth survey, the author identified four main problems: the use of chemicals in agriculture, inappropriate educational curriculum, and less than optimal innovation and marketing of MSME products. The implementation method involves face-to-face (on the spot training) with coordination of village officials, as well as the use of chemical raw materials and promotional media to support marketing. The results of the activity show that the author understands the importance of effective communication in building relationships with the community and gaining valuable experience outside the classroom. MSME actors feel helped by the support of students, while the community feels a more lively village atmosphere. This activity is expected to provide significant benefits for the community of Desa Besar II Terjun and be the first step in sustainable empowerment.